Modeling of single mixed refrigerant process for offshore natural gas liquefaction - Syed Ahmad Farhan , Syed Ab Mutalib (2011)
The main objective of this thesis is to model a single mixed refrigerant process for offshore natural gas liquefaction using ASPEN HYSYS as a simulation tools.The liquefaction process employed in this part is a result of modification of previous case done by C.W.Remeljeja and A.F.A.Hoadley (2004). This work is divided into two sections.First is to model the PRICO LNG process that published result.Second is to improve the model by adding the mixer in the mixed refrigerant stream after the separator.It allows two different phase of gas and liquid of mixed refrigerant to mix together before entering the LNG Heat Exchanger (cold box).The mixer also helps to maintain a constant flow rate of the stream to the cold box.The results are obtained after the system is converged.When modeling the PRICO process in Aspen Hysys,certain variables such as temperature and pressure at the streams entering and leaving the cold box cannot be changed directly.This will cause temperature cross and change of mixed refrigerant phase in the respected stream.As a result,by doing structural modification on the basic PRICO process specifically in case 3,the load duty of the compressor can be lowered significantly.After three different structural modifications discussed in this paper, the compressor duty to liquefy the natural gas can be reduced down to 82300.46 kW when compared to the base case. As a conclusion,structural modification in case 3 is the best model when compare case 1 and case 2 because it operates in lowest compressor duty.For the future improvement,a different structure modification can be done using case 3 as a base model,for example replacing the valve with a multiphase expander to generate electricity in this LNG liquefaction process.